SPIRITUAL SPACE: SCIENTIFIC AND PHILOSOPHICAL ANALYSIS (The Journal of Interdisciplinary Human Studies, 2025)
This article analyzes the concept of spiritual space from a scientific and philosophical perspective. It explores the philosophical essence of spiritual space, its connection with human consciousness and spirituality, as well as its role in society and culture. The article examines the factors influencing the formation of spiritual space, in particular, issues such as values, beliefs, and spiritual heritage. It also analyzes the impact of spiritual space on a person’s personal and social life, its importance in spiritual development and self-awareness. In conclusion, the article substantiates the relevance of preserving and developing spiritual space.
Keywords: spiritual space; enlightened society; spirituality; philosophy; scope; national values; social life